(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
أجريت دراسة ترسيبية مفصلة للقطاع الجنوبي من الرصيف القاري السوري (N : 35.16022 E 35.92712 N 34.71354 E 35.94267) بغية تحديد طبيعة، وتوزع وخصائص الرسوبيات البحرية الموزعة على كامل هذا القطاع. أظهرت دراسة العينات الرملية الشاطئية وجود تغاير لوني لرسوبيات المنطقة الواحدة مما يدل على المصادر المتنوعة لهذه الرسوبيات مستمدة في معظمها من المناطق الواقعة خلف الساحل. بينت العينات القاعية العميقة وجود ستة نماذج رسوبية ألا وهي: رمال؛ طين رملي؛ رمال حصوية بنسبة ضئيلة؛ رمال طينية حصوية بنسبة ضئيلة؛ طين رملي حصوي بنسبة ضئيلة؛ وأخيراً حصى. دلت النتائج على أن الرسوبيات المدروسة ذات حجم حبيبي متوسط، ذات فرز معتدل جيد، ذات ميل سلبي جداً وأخيراً متوسطة التفرطح. تؤكد هذه المعطيات على أن الترسيب قد حدث تحت تأثير ظروف طاقية معتدلة إلى عالية تتغير من مكان لآخر حسب طبيعة منطقة الترسيب وحجم وطبيعة المواد الموجودة في بيئة الترسيب من جهة، وتبعاً لشدة الطاقة المحركة للرسوبيات والمتمثلة في التيارات البحرية، الدوامات البحرية، وطبيعة الأمواج والمد والجزر من جهة أخرى. Detailed sedimentary study of the Southern section of the Syrian Continental shelf (N 35.16022 E 35.92712: N 34.71354 E 35.94267) has been carried out in order to determine the sediment nature and distribution. The study of coastal sandy samples (from beach to 2m water depth) revealed variation in the sand colours from place to place. This indicates that there are many sources for coastal sand mostly derived from the hinterlands. Six sediment sorting types were identified along the continental shelf and these are: Sand; Sandy Mud; Slightly Gravelly Sand; Slightly Gravelly Muddy Sand; Slightly Gravelly Sandy Mud; and Gravel. The textural studies clearly establish that the sediments are of medium grain size, moderately well sorted, very negatively skewed and mesokurtic. These parameters confirm that the sediments were deposited under moderate to high energy conditions. These conditions vary from place to another according to the place of deposition and the nature of the source material on one hand and the severity of the kinetic energy namely ocean currents, marine eddies, waves and tides on the other hand.